FORTIDSBRUG OG FØLELSER - REENACTERES FORTIDSSIMULATIONER OG HÅNDTERING AF 2. VERDENSKRIG - Brædder, Anne (Temp - tidsskrift for historie, 2018)
The article examines the relation between memory and emotions. Employing Sarah Ahmed’s ideas on ’sticky feelings’ and Arlie Hochschild’s ’emotional labour’ it is analysed how WWII reenactors portraying German, British and American soldiers and Danish resisters simulate and handle a past connected with feelings as well as a powerful collective memory. The empirical material consists of interviews with reenactors and observations done at public WWII reenactment events in Denmark. The body is in focus of the analysis of the reenactors’ emotional and memory practices. The reenactors’ choice of war actors they embody, what parts of the war they bodily simulate and what embodied movements they do are analysed as emotion management of WWII so they are done in accordance with what the reenactors presume are appropriate to the other reenactors, the museums hosting the reenactment events and the guests at the events. The reenactors’ engagement with WWII must be understood taking both emotions and the memory context the reenactment activity is played out in into account. Thus, the author argues for a greater exchange between memory studies and history of emotions where the relation between power, time, emotions and memory are examined.